Coping and Resilience Are Differently RelatedDepending on the Population: A Comparison Between Three Clinical Samples and the General Population - Rodríguez Rey, Rocio; Garrido Hernansaiz, Helena; Alonso Tapia, Jesús (My University)
Este estudio explora la relación entre las estrategias de afrontamiento y la resiliencia frente a distintas situaciones estresantes.

Different stressors trigger different coping strategies, and resilience also varies across adversities. This study aimed to investigate the association between coping strategies and resilience outcomes in different stressful situations. Individuals living with HIV, those with cancer, those who have children with cancer, or those from the general population (N= 525) completed measures of resilience (the Brief Resilience Scale) and coping (the Situated Coping Questionnaire for Adults). We examined differences in resilience and in the use of coping strategies across samples with analyses of variance. We obtained high- and low-resilience groups for each sample and conducted analyses of variance to study differences in coping strategies. Result showed that resilience was similar across samples, but differences emerged regarding coping strategies (e.g., individuals with HIV were more likely to use emotional expression and isolation and less likely to seek help). The HIV high- and low-resilience groups used every strategy differently, except for problem-solving and thinking avoidance. Cancer high- and low-resilience groups differed only in rumination. Parents of children with cancer differed in rumination, self-blame, isolation, and positive thinking. General population groups differed in all strategies but help-seeking. In conclusion, as different strategies were associated with resilience for each sample, interventions tailored for specific problems should, therefore, be implemented.
Artículos en revistas